1997
DOI: 10.1177/089686089701700207
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Sclerosis in Chronic Peritoneal Dialysis Patients: Analysis of Clinical Presentation, Risk Factors, and Peritoneal Transport Kinetics

Abstract: Objective To analyze clinical features of peritoneal sclerosis (PS) in a group of peritoneal dialysis (PD) patients, and to compare potential risk factors and peritoneal transport characteristics with a control group matched for duration of PD. Design Study 1: Retrospective study of 16 PD patients with PS. Study 2: Case-control study comparing 10 patients with evident PS to 30 control patients who were matched for duration of PD. Setting Continuous Ambulatory Peritoneal Dialysis unit in the Academic Medical Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
129
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 39 publications
4
129
0
3
Order By: Relevance
“…The pathophysiology of EPS is largely unknown, but several factors, such as long-term PD, high dialysate/ plasma creatinine ratio (D/P Cr), high serum beta-2 microglobulin (b2MG), PD-associated peritonitis and the effects on the peritoneal membranes of exposure to non-physiological levels of glucose and pH, have been suggested to predispose patients to devel-oping EPS (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Among these etiological factors, the duration of PD therapy is thought to be the most important risk for developing EPS (1,(13)(14)(15). One study from Australia assessed the effect of increasing duration of PD on the prevalence of EPS, and found that EPS increased with the duration of PD from 1.9% for patients on dialysis >2 years to 6.4%, 10.8% and 19.4% in patients on PD for greater than 5, 6 and 8 years, respectively (1).…”
mentioning
confidence: 99%
“…The pathophysiology of EPS is largely unknown, but several factors, such as long-term PD, high dialysate/ plasma creatinine ratio (D/P Cr), high serum beta-2 microglobulin (b2MG), PD-associated peritonitis and the effects on the peritoneal membranes of exposure to non-physiological levels of glucose and pH, have been suggested to predispose patients to devel-oping EPS (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Among these etiological factors, the duration of PD therapy is thought to be the most important risk for developing EPS (1,(13)(14)(15). One study from Australia assessed the effect of increasing duration of PD on the prevalence of EPS, and found that EPS increased with the duration of PD from 1.9% for patients on dialysis >2 years to 6.4%, 10.8% and 19.4% in patients on PD for greater than 5, 6 and 8 years, respectively (1).…”
mentioning
confidence: 99%
“…Initially, the ease with which UF could be achieved with the frequent use of 3.86% glucose exchanges led to the myth that fluid balance could be better achieved on CAPD than on hemodialysis (HD) and that ad libitum fluid intake may be possible. It is now accepted that this is not so and that excessive glucose use and exposure may lead to membrane damage and loss of UF (37). In this retrospective analysis, patients with peritoneal sclerosis had a greater cumulative glucose exposure than did their controls matched for duration of dialysis.…”
Section: Fluid Balance During Capdmentioning
confidence: 79%
“…The evidence that increased glucose use leads to membrane failure is both direct and indirect. The pathogenetic role for glucose in the development of peritoneal sclerosis was suggested in a case-controlled study in which CAPD patients with sclerosis had a greater cumulative glucose exposure than did the controls matched for duration of CAPD, the difference being present during the first year in the majority (37). Further indirect evidence comes from the same group.…”
Section: Management In Pd Patientsmentioning
confidence: 99%
“…Although the evidence is principally circumstantial, there has been a general consensus in the PD community that ''glucose-sparing'' regimens need to be used to protect the long-term health of the peritoneal membrane. Although an association between the use of more hypertonic dialysate and the subsequent development of ultrafiltration failure and encapsulating peritoneal sclerosis has been proposed (20), it is difficult to dissociate cause and effect. In other words, patients who are inflamed and rapid transporters from the outset would need to use more hypertonic dialysis fluid, and they are also the same patients at risk for ultrafiltration failure and membrane alterations independent of the exposure to glucose and GDPs.…”
Section: Effects On the Peritoneal Membranementioning
confidence: 99%